1997
DOI: 10.1017/s0956792597003197
|View full text |Cite
|
Sign up to set email alerts
|

Source-type solutions to thin-film equations in higher dimensions

Abstract: We prove that the thin film equation ht+div (hn grad (Δh))=0 in dimension d[ges ]2 has a unique C1 source-type radial self-similar non-negative solution if 0<n<3 and has no solution of this type if n[ges ]3. When 0<n3 the solution h has finite speed of propagation and we obtain the first order asymptotic behaviour of h at the interface or free boundary separating the regions where h>0 and h=0. (The case d=1 was already known [1]).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 22 publications
3
76
0
Order By: Relevance
“…In some sense, these terms slow down the dynamics and move the symmetry point to infinity in de-singularized coordinates, which makes the construction of solutions by a shooting argument, starting at the contact line, less accessible and a shooting argument as in [22], starting at the point of symmetry, more favorable.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…In some sense, these terms slow down the dynamics and move the symmetry point to infinity in de-singularized coordinates, which makes the construction of solutions by a shooting argument, starting at the contact line, less accessible and a shooting argument as in [22], starting at the point of symmetry, more favorable.…”
Section: 2mentioning
confidence: 99%
“…Existence, uniqueness, and leading-order asymptotics of this problem were studied by Bernis and Ferreira in [22] under the assumption…”
Section: Appendix a Higher Dimensionsmentioning
confidence: 99%
“…This case is nonphysical but bears the same features as the original system and admits a selfsimilar analytical solution, 19 which can be used to assess the validity of the numerical solution. Diez and Kondic 11 showed that for an initial profile which approximates the delta function and Neumann boundary conditions, the evolution of the maximum film thickness h val satisfies Figure 3 shows the analytical and numerical solutions with V val = 3 and a 0.01 thick precursor film.…”
Section: Validation Of the Solution Proceduresmentioning
confidence: 99%
“…Ferreira and Bernis [14] study the equation in higher space dimensions: u t = −∇ · (u n ∇∆u). They consider radially-symmetric solutions and find that if 0 < n < 3 there exist compactly supported source-type solutions with zero contact angles.…”
Section: 2mentioning
confidence: 99%
“…The authors present three methods for solving the ODEs that the profiles U must satisfy. They use fixed point arguments (as in [14]) to prove the existence of the source-type solutions. They use a shooting argument to find the dipole solutions in the n = 1 case.…”
Section: 2mentioning
confidence: 99%